2018
DOI: 10.1016/j.msea.2017.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure on the impact toughness transition temperature of direct-quenched steels

Abstract: A sufficient level of toughness at low temperatures is paramount for the use of structural steels intended for arctic applications. Therefore, it is important for the steel industry to identify the factors that control brittle fracture toughness. In this study, the quantitative effect of microstructure on the impact toughness transition temperature has been investigated with 18 different thermomechanically rolled and direct-quenched low-carbon ultra-high-strength steels with varying martensite and bainite cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…The 0Mo steel showed clear {110}<110> and {011}<100> components, but exhibited only weak {112}<131> and {554}<225> components, see Figure 10a. In previous studies, it has been noticed that {110}<110> texture components can enhance the propagation of cleavage fracture and thus decrease low-temperature toughness [17]. The better properties of Mo alloyed steels can also be a result of boron protection.…”
Section: Correlation Between Mechanical Properties and Microstructural Featuresmentioning
confidence: 99%
“…The 0Mo steel showed clear {110}<110> and {011}<100> components, but exhibited only weak {112}<131> and {554}<225> components, see Figure 10a. In previous studies, it has been noticed that {110}<110> texture components can enhance the propagation of cleavage fracture and thus decrease low-temperature toughness [17]. The better properties of Mo alloyed steels can also be a result of boron protection.…”
Section: Correlation Between Mechanical Properties and Microstructural Featuresmentioning
confidence: 99%
“…Previous studies have shown that the impact transition temperature is controlled by the largest grains in the grain size distribution, where grain size refers to the ECD of grains with grain boundary misorientations > 15°, for example d90%. 20,21 By alloying with Nb-Mo, a pancaked austenite structure was achieved after hot rolling, which then produced a finer and more uniform prior austenite structure after re-austenitization, presumably due to the presence of more nucleation sites for austenite grains. This led to a finer martensitic structure with higher strength and better impact toughness.…”
Section: Mechanical Properties After Hot Rolling Direct Quenching Anmentioning
confidence: 99%
“…On the refining effect of B removal on grain size, Gao et al [44] made similar findings and proposed that austenite grain size increases with increased boron content due to the formation of BN, which reduces the amount of grain refining AlN. Pallaspuro et al [43] showed the importance of grain refinement and a correlation between toughness and martensite content for martensitic-bainitic high-strength steels, where an almost linear decrease in toughness with increasing martensite content was found. However, the results of the current study concern martensitic-ferritic steels instead of martensitic-bainitic steels.…”
Section: Accepted Manuscriptmentioning
confidence: 83%